DIGITAL TECHNIQUES FOR MONITORING CHANGES IN WATER-BODY USING SATELLITE IMAGE - Ali, Saleh (Iraqi Journal of Science, 2024)
In this paper, two pairs of temporal TM, and ETM+ (28.5 spatial resolution) images have been used to detect the change in water body. The first study area was the (Mosul Aski Dam, 1984 to 2002) in the upper Jazirah (located approximately 60 km northwest of Mosul city), the geographic corners coordinates was (Lat. 36° 37´ 30˝ to 36° 55´ 00˝ N, Long. 42° 30´ 00˝ to 43° 00´ 00˝ E). The second was the area of remaining Marshland areas (Hawr Al-Hawizeh /Al-Azim, 2000 to 2002), the geographic corners coordinates was (Lat. 31° 44´ 13.62˝ to 31° 26´ 32.5˝ N, Long. 47° 27´ 0.32˝ to 47° 50´ 00˝ E), Southern East of Iraq. Image to map registration with first order polynomial has been adapted to correct images from geometric errors. An adaptive matching technique (depend upon the UTM coordinates projection) has been performed to match the two temporally images. Three digital algorithms have been utilized to detect the change between the two images; i.e. image differencing, image ratioing, and PCA methods. The total RMS error (registration & matching process) was less than 1 meter.